2018
DOI: 10.1007/s00284-018-1508-y
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Thermostable Direct Hemolysin and Biofilm Formation of Vibrio parahaemolyticus by Quorum-Sensing Genes luxM and luxS

Abstract: Vibrio parahaemolyticus is a seafood opportunistic pathogen. There are evidences suggesting that virulence skills, including hemolytic activity and biofilm formation, are regulated by the luxM/luxS-dependent quorum-sensing system in V. parahaemolyticus, and their regulatory mechanism is not well understood. To better understand the virulence regulatory mechanism of V. parahaemolyticus, the luxM deletion (△luxM) and luxS deletion (△luxS) mutants were constructed and their impacts on growth, hemolysin activity, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 40 publications
0
15
0
Order By: Relevance
“…Another study has shown that the luxM/luxS-dependent quorum sensing mediates the regulation of the hemolytic activity along with biofilm formation in V. parahaemolyticus. luxM downregulates tdh gene expression, and therefore compromises the hemolytic activity, while luxS upregulates the expression of the hemolysin (Guo et al, 2018). Also, HN-S (nucleoid-associated DNA binding regulator) and Hfq (a global transcription regulator) have been shown to repress the production of TDH (Nakano et al, 2008;Sun et al, 2014).…”
Section: Secretion and Regulation Of Tdhmentioning
confidence: 99%
“…Another study has shown that the luxM/luxS-dependent quorum sensing mediates the regulation of the hemolytic activity along with biofilm formation in V. parahaemolyticus. luxM downregulates tdh gene expression, and therefore compromises the hemolytic activity, while luxS upregulates the expression of the hemolysin (Guo et al, 2018). Also, HN-S (nucleoid-associated DNA binding regulator) and Hfq (a global transcription regulator) have been shown to repress the production of TDH (Nakano et al, 2008;Sun et al, 2014).…”
Section: Secretion and Regulation Of Tdhmentioning
confidence: 99%
“…The QS system consists of signals and receptors, quorum sensing regulators, and other genes under control. The fold difference of opaR upregulated was about 2.08, and luxS was downregulated by about 2.32 ( Guo et al., 2018 ) ( Table 2 ). opaR is considered a major QS regulator involved in colony morphology, virulence and other biophysical aspects ( Burke et al., 2015 ), and LuxS is a key enzyme in the LuxS/AI-2 QS system.…”
Section: Resultsmentioning
confidence: 99%
“…We observed that the promoter activity of P epsA - lux and P mfpABC - lux were all decreased significantly in Δ robA Δ opaR and Δ robA Δ cpsQ compared to that in the WT and Δ robA strains ( Figures 6E,F ). V. parahaemolyticus can produce three types of autoinducer, including harveyi autoinducer 1, autoinducer 2, and cholerae autoinducer 1, which are synthesized by LuxM, LuxS, and CqsA, respectively ( Guo et al, 2018 ; Wu K. et al, 2019 ). To explore which autoinducer participates in the regulation of RobA to OpaR and CpsQ, we then created a series of genes deletion mutants of the autoinducer synthases.…”
Section: Resultsmentioning
confidence: 99%